PENGELOLAAN MOBIL DINAS OLEH BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA PEKANBARU TAHUN 2018 - Panji Afrianto; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Management of official cars is an implementation of management activities for government-owned cars and is used for the purpose of carrying out work for regional work units. Based on Mayor Regulation Number 118 of 2016 concerning Position, Composition, Organization, Duties and Functions and Work Procedures of the Regional Financial and Asset Management Agency (BPKAD), it has the authority to manage official cars in Pekanbaru City. The problem of this research is that the management of official cars in Pekanbaru City has not been optimal in 2018.The purpose of this study is to determine the management of official cars by the Regional Financial and Asset Management Agency of Pekanbaru City in 2018. The theoretical concept that the author uses for the management of official cars according to Mardiasmo in his book Autonomy and Regional Financial Management. This research uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniquesThe results of this study are first, the management of official cars by BPKAD Kota Pekanbaru in 2018 has been carried out but is not optimal because first, official cars that are in a badly damaged condition can no longer be proposed for maintenance because the goods that are in a badly damaged condition must be submitted to the manager for immediate removal. . Second, there is an overlap in the number of proposed maintenance and the cost of maintaining the budgeted assets. Third, BPKAD has taken control of official cars controlled by former officials. However, even though BPKAD has carried out the control, there are still official cars that have not been successfully controlled.Furthermore, the factors inhibiting the management of official cars by the Regional Financial and Asset Management Agency of Pekanbaru City in 2018 are: First, the low competence of human resources (HR). Second, there is a lack of coordination between asset managers and users of goods. Third, the low budget rationalization for the Management of Official Cars by the Regional Financial and Asset Management Agency of Pekanbaru City in 2018Keywords: Management, Official Car, Regional Financial and Asset Management Agency